2023
DOI: 10.1002/chem.202203438
|View full text |Cite
|
Sign up to set email alerts
|

Cooperativity‐Driven Reactivity of a Dinuclear Copper Dimethylglyoxime Complex

Abstract: In this report, we present the dinuclear copper(II) dimethylglyoxime (H2dmg) complex [Cu2(H2dmg)(Hdmg)(dmg)]+ (1), which, in contrast to its mononuclear analogue [Cu(Hdmg)2] (2), is subject to a cooperativity‐driven hydrolysis. The combined Lewis acidity of both copper centers increases the electrophilicity of the carbon atom in the bridging μ2‐O−N=C‐group of H2dmg and thus, facilitates the nucleophilic attack of H2O. This hydrolysis yields butane‐2,3‐dione monoxime (3) and NH2OH that, depending on the solvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(31 citation statements)
references
References 75 publications
2
24
0
Order By: Relevance
“…[15,39,41,43] In contrast, the usage of Cu(ClO 4 ) 2 • 6H 2 O or Cu(BF 4 ) • 6H 2 O (ratio 1 : 1 or 1 : 2, Cu 2 + : H 2 dmg) leads to the formation of the dinuclear species 2 a. [17][18][19]39,40] Thus, even though both anions used are weakly coordinating and accordingly, a similar reaction outcome could have been expected, there are clear preferences for the product formation. These preferences presumably are caused by the basicity of the anions as the basic anion OAc À yields mononuclear 1, whereas the neutral anions ClO 4 À and BF 4 À (as well as SO 4 2À ) favor formation of dinuclear 2 a.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…[15,39,41,43] In contrast, the usage of Cu(ClO 4 ) 2 • 6H 2 O or Cu(BF 4 ) • 6H 2 O (ratio 1 : 1 or 1 : 2, Cu 2 + : H 2 dmg) leads to the formation of the dinuclear species 2 a. [17][18][19]39,40] Thus, even though both anions used are weakly coordinating and accordingly, a similar reaction outcome could have been expected, there are clear preferences for the product formation. These preferences presumably are caused by the basicity of the anions as the basic anion OAc À yields mononuclear 1, whereas the neutral anions ClO 4 À and BF 4 À (as well as SO 4 2À ) favor formation of dinuclear 2 a.…”
Section: Resultsmentioning
confidence: 96%
“…As this exclusive formation of 5 starting from CuCl 2 (• 2H 2 O) is consistent with literature, we excluded it from further investigations. [16,18] As a side note, with regard to Cu(ClO 4 ) 2 • 6H 2 O and subsequent formation of 2 a, it was observed that excess H 2 dmg stabilizes 2 a against the reported hydrolysis [39] as these reaction mixtures required more time to yield the hydrolysis products than those with fewer amounts of H 2 dmg. In general, the results reflect the synthetic protocols, i.e.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations